Does Fintech Adoption Enhance Banks’ Sustainability Performance? Competitiveness As A Mediator - Kunwar, Kripa; Bhandari, Dipak Bahadur; G.C, Surya Bahadur (The Lumbini Journal of Business and Economics, 2025)
Purpose: The study intends to investigate the impact of Fintech adoption and competitiveness on sustainability performance of the banks in Nepal. Methods: The study is based on data collected from 209 bankers through a structured questionnaire in Nepal employing a convenience sampling technique. Additionally, to examine the hypothesized relationship between variables, the study applied the Partial least square structural equation modelling (PLS-SEM) for data analysis. Results: The results demonstrate that Fintech adoption have a positive and significant (β = .218; P ˂ .01) impact on sustainability performance of bank, and also confirms the partial mediating effect of competitiveness (β = .141; P ˂ .01) within the relationship. Conclusion: The study concludes that a bank can improve sustainability performance through the Fintech adoption. In addition, Fintech adoption enhances the competitiveness of the bank, which leads to improved sustainability performance. The study highlights the significance of Fintech adoption in improving sustainability performance. Moreover, this study will offer pivotal insights to the bank manager and regulator to develop a more inclusive and resilient banking system through Fintech adoption in Nepal.